Isolation Of Vibrio Cholera O1 During an Outbreak of Acute Gastroenteritis In Dahod District, Gujarat - Barve, Sonia; Javadekar, T B; Nanda, Sandeep; Pandya, Chandresh; Pathan, Amjad; Chavda, Parag (National Journal of Community Medicine, 2012)
Background: Epidemics of cholera caused by Vibrio cholerae O1 or O139 have been reported from different parts of India. It is necessary to investigate Acute Gastroenteritis cases for the presence of V. Cholerae by stool sample analysis in the reference laboratory. Objectives: To analyze stool samples for the presence of V. cholerae and subtypes in confirmed cases of cholera during an outbreak of Acute Gastroenteritis. Materials and Methods: During an outbreak of Acute Gastroenteritis, total 171 stool samples and 5 water samples were collected by local health authorities and sent to the Microbiology Department, Medical College, Baroda for the analysis. Results: Out of total 171 stool samples, 46 stool samples were found positive (27%) for V. cholerae O1 biotype El Tor, serotype Ogawa as a sole pathogen. Highest positivity (50%) was found in age group of 0-15 years. Positivity rate was same among both the genders. Water samples showed presence of coliform bacilli with high MPN (most probable number) count. Faecal coliform was also found in both the water samples. Conclusion: V. cholerae O1 biotype El Tor, serotype Ogawa was confirmed as a sole pathogen in stool samples confirm the cholera outbreak and water contamination was supported by the presence of Faecal coliform organisms in water samples.